Rapid and economical method for species identification of clinically significant coagulase-negative staphylococci. - Ieven, M (1995)
Four methods for the species identification of coagulase-negative staphylococci in the medical microbiology laboratory were compared with 444 consecutive isolates. The methods included (i) the reference method based on growth tests, (ii) API ID 32 Staph (bioMérieux), (iii) Staph-Zym (Rosco), and (iv) a rapid 4-h method developed in our laboratory (UZA method). The last method is based on the detection within 4 h of enzymatic activity of heavy bacterial suspensions in three substrate solutions (nongrowth tests). For 16.5% of the isolates some supplementary growth tests read after 24 h had to be added to the enzyme data for satisfactory identification. The reference method failed to identify four isolates. Of the 440 isolates identified by the reference method, API ID 32 Staph, Staph-Zym, and the UZA method correctly identified 419 (95.2%), 429 (97.5%), and 430 (97.7%) and misidentified 8 (1.8%), 4 (0.9%), and 1 (0.2%), respectively. Staphylococcus epidermidis, S. haemolyticus, S. lugdunensis, S. schleiferi, and S. capitis were identified with an accuracy of 98 to 100% by all the systems tested. S. capitis subsp. ureolyticus was not recognized by the API ID 32 system because the biochemical profiles for it are not yet included in the corresponding database. Whereas API ID 32 identified all 13 S. warneri isolates, both Staph-Zym and the UZA method missed 2 of these. S. hominis was identified with the least accuracy by the API ID 32 system (26 of 39 isolates), whereas the UZA and Staph-Zym methods identified 36 of the isolates belonging to this species.(ABSTRACT TRUNCATED AT 250 WORDS)